THE EFFECT OF PROJECT MANAGER COMPETENCE ON THE ACHIEVEMENT OF CONSTRUCTION PROJECT PERFORMANCE - Muhammad Fauzan Surya; Anita Rauzana; Alfa Taras Bulba (Jurnal Impresi Indonesia, 2024)
The development of the construction services sector in Indonesia continues to experience rapid growth, encouraging construction industry players to have quality human resources. This research aims to identify project manager competency factors on construction projects in Banda Aceh City, analyse the relationship between these and project performance achievements, and evaluate their influence on construction project performance achievements in Banda Aceh City. The object of this research is the competency factors of project managers that influence construction project performance. This research was conducted at contractor companies domiciled in the Banda Aceh City area. The data sources used in this research are primary data and secondary data. The population of contractors at small, medium and large qualification levels is 71 contractors. The total sample was 42 contractors. The sampling technique used was purposive sampling. The variables used in this research include the independent variable (X) and the dependent variable (Y). The data analysis used in this research is descriptive, simple correlation analysis and multiple linear regression analysis. The research results show that knowledge, skills, and attitudes have a solid relationship. In contrast, management has a high relationship with project performance achievement. Overall, the project manager's competency factor significantly affects project performance, reaching 94.9%. Management is the most dominant competency factor influencing the achievement of project performance in Banda Aceh City. Thus, increasing the competence of project managers, especially in management, is expected to improve the quality of construction project implementation in the region.